Correlation Between the Immediate Remnant Stump Length and Vein Diameter After Cyanoacrylate Closure Using the VenaSeal System During Treatment of an Incompetent Great Saphenous Vein. (January 2020) - Park, Insoo; Kim, Daehwan
Objectives: Cyanoacrylate glue is injected for incompetent great saphenous vein (GSV) treatment 5 cm distal to the saphenofemoral junction (SFJ). Although a few reports have investigated the postprocedural remnant stump length, none have focused on the factors affecting glue extension length and the consequent remnant stump length. Methods: Seventy-nine patients undergoing cyanoacrylate closure using the VenaSeal system at our clinic between August 2018 and November 2018 were investigated. The GSV diameter was measured just before treatment in the supine position 3 cm distal to the SFJ. Cyanoacrylate glue was injected 5 cm distal to the SFJ. Results: The mean glue extension length was 1.13 ± 1.12 cm. The GSV diameter and glue extension length exhibited a significant inversely proportional relationship ( P < .001). More specifically, patients with a GSV diameter ≥0.7 cm had a longer remnant stump length than those with a smaller GSV diameter ( P < .001). Conclusions: An increased GSV diameter is likely associated with a decreased glue extension length and, consequently, a longer remnant stump.